INCREASING OF ACCURACY FOR DENSITY MEASUREMENT MAKING BY A RADIOISOTOPIC BASIS WEIGHT SENSOR - O. L. Ermakovich; G. A. Lisovsky; P. V. Kuchynski; I. A. Titovitsky (Приборы и методы измерений, 2015)
The experimental investigations of spatial energy distribution for beta particles in a measuring gap of a basis weight sensor are described. We propose the measurement procedure, which employs a local domain of the ionization chamber input window. The average scattering angles in polyethylenterephtalate films are determined. Suggested technical solutions allow more then three times to reduce the error of measuring of radioisotope densitometer.